(untitled) (Journal of Civil Engineering Researchers, 2023)
In recent decades, Geopolymer concrete (GPC) is a new material in the construction industry, which has favorable performance and workability and contains aluminosilicate materials full of silicate (Si), aluminum (Al), and alkaline solution as a binder. The advantages of using geopolymer materials instead of cement in concrete are not limited to high mechanical and microstructural properties. It also has a remarkable effect in reducing greenhouse gas emissions. In the current study, Granulated Blast Furnace Slag (GBFS) GPC was used with 0-2% polyolefin fibers (POFs) and 0-8% nano-silica (NS) to improve its structure. After curing the specimens under dry conditions at a temperature of 60 °C in an oven, they were subjected to compressive strength, tensile strength, elastic modulus, ultrasonic pulse velocity (UPV) and impact resistance tests to evaluate their mechanical properties. The addition of NS enhanced the whole properties of the GBFS geopolymer concrete. The compressive strength, tensile strength, and elastic modulus of the concrete increased by up to 22%, 14%, and 24%, respectively. Besides, it leads to ultrasonic wave velocity enhancement to 12% in the room temperature. The addition of the fibers to the GPC significantly increased the tensile strength (by up to 9%) and the energy absorbed due to the impact. Moreover, compared to Concrete containing ordinary portland cement (OPC), the GPC demonstrated much better mechanical and microstructural properties. Besides, the presence of POFs in the GPC compound substantially affects tensile strength and resistance against an impact. Accordingly, the sample’s tensile strength had an improvement by 8.4% in the room temperature. In the following, by conducting the X-Ray Fluorescence (XRF), X-Ray Diffraction (XRD), and Scanning electron microscope (SEM) tests, a microstructure investigation was carried out on the concrete samples. In addition to their overlapping with each other, the results indicate the GPC superiority over the regular concrete.